Atividades pedagógicas específicas para crianças com dificuldades de aprendizagem - Ventura, Mariana Bizarro [UNESP]; Osti, Andréia [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This paper is a part of a larger project which dedicates to provide educational assistance to children with learning difficulties from public schools. Here we will present some of the activities that were developed in the Extension Project entitled: "Teacher training for specialized educational services to students with learning difficulties" with its objective of developing fine motor skills . The service was and continues on being done done with a child of the second grade of elementary school who was still in pre- syllabic stage in their literacy , in other words, the child was not writing according what is expected from the grade. Research on psychomotricity helped understanding the importance of encouraging movement practice in all stages of a child's life to help with the learning process.

O presente trabalho é parte de um projeto maior que se dedica a prestar atendimento pedagógico para crianças de escolas públicas com dificuldades de aprendizagem. Aqui serão apresentadas algumas das atividades desenvolvidas nos atendimentos do Projeto de Extensão: “Formação de professores para o atendimento educacional especializado a alunos com dificuldades de aprendizagem” e que tinham por objetivodesenvolver a coordenação motora fina. O atendimento foi e está sendo realizado com uma criança do segundo ano do Ensino Fundamental que ainda estava na fase pré- silábica em sua alfabetização, ou seja, ainda não estava escrevendo dentro do esperado para a série. Pesquisas sobre a psicomotricidade ajudaram a compreender a importância de incentivar a prática do movimento em todas as etapas da vida de uma criança para ajudar no processo de aprendizagem.
Keywords: Educational activities; Literacy; Psychomotricity; Atividades pedagógicas; Alfabetização; Psicomotricidade